From the concept of organizational adaptation to strategies for adaptation of tourism organizations and businesses - Anichiti, Alexandru; Butnaru, Gina Ionela (Revista de turism - studii și cercetări în turism, 2020)
Due to increasing competition and rapid developments in terms of technology, an organization must adapt to the changing environment in order to survive, grow and develop. The aim of this paper is to analyze the relationships between organizational adaptation in tourism firms and strategies for adaptation to the external factors of tourism firms. In order to accomplish our research objective, we reviewed the literature on organizational adaptation as concerned with making adjustments over the lifespan of an organization, its strategies and focus as the venture and the marketplace evolves. Adaptation is defined as an organization’s capacity to adapt, and is related to how it adapts and what strategies does it use to adapt. A conceptual model and hypotheses are proposed. Results from a survey of small business founders/owners from the Suceava region are used to test multiple hypothesis.